Antiviral Drugs Against Severe Fever With Thrombocytopenia Syndrome Virus Infection - Takayama-Ito, Mutsuyo; Saijo, Masayuki (Frontiers in microbiology, 2020)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease caused by SFTS virus (SFTSV), which is a novel bunyavirus. SFTSV was first isolated from patients who presented with fever, thrombocytopenia, leukocytopenia, and multiorgan dysfunction in China. Subsequently, it was found to be widely distributed in Southeast Asia (Korea, Japan, and Vietnam). SFTSV can be transmitted not only from ticks but also from domestic animals, companion animals, and humans. Because the case fatality rate of SFTS is high (6-30%), development of specific and effective treatment for SFTS is required. Studies of potential antiviral drugs for SFTS-specific therapy have been conducted on existing or newly discovered agents and , with ribavirin and favipiravir being the most promising candidates. While animal experiments and retrospective studies have demonstrated the limited efficacy of ribavirin, it was also speculated that ribavirin would be effective in patients with a viral load <1 × 10 copies/mL. Favipiravir showed higher efficacy than ribavirin against SFTSV in assays and greater efficacy in animal models, even administrated 3 days after the virus inoculation. Although clinical trials evaluating the efficacy of favipiravir in SFTS patients in Japan are underway, this has yet to be confirmed. Other drugs, including hexachlorophene, calcium channel blockers, 2'-fluoro-2'-deoxycytidine, caffeic acid, amodiaquine, and interferons, have also been evaluated for their inhibitory efficacy against SFTSV. Among them, calcium channel blockers are promising because in addition to their efficacy and , retrospective clinical data have indicated that nifedipine, one of the calcium channel blockers, reduced the case fatality rate by >5-fold. Although further research is necessary to develop SFTS-specific therapy, considerable progress has been achieved in this area. Here we summarize and discuss recent advances in antiviral drugs against SFTSV.